Analysis Of The Causes Of Pending Bpjs Health Claims At Melania Bogor Hospital - Riastiningsih, Sari; Andriyani, Andriyani; Suherman, Suherman; Srisantyorini, Triana; Dwana, Laksmita (International Journal Labs, 2025)
This study analyzes the causes of pending BPJS Kesehatan claims at Melania Bogor Hospital, emphasizing the complex interplay of human resources, document completeness, and operational procedures. The research identifies that a significant factor contributing to pending claims is the limited capacity of the Casemix team, with only one member having received external training in claims coding. Additionally, inaccuracies in medical documentation, such as unclear diagnoses and incomplete supporting documents, hinder the claims process. The absence of a comprehensive hospital information system (SIMRS) for automatic validation further exacerbates the issue. The findings reveal that pending claims not only disrupt the hospital's cash flow but also increase the workload for administrative staff, leading to delays in service provision. This research underscores the need for improved training, enhanced documentation practices, and better integration of digital systems to ensure timely processing of claims and maintain the quality of health services.